COMPLIANCE OF THE PROSPECTIVE BRIDES AND GROOMS IN LABORATORY EXAMINATIONS AND PREMARITAL COUNSELING IN THE WORKING AREA OF MUTIARA BARAT HEALTH CENTER, PIDIE REGENCY - Noviyati, Ike; Amin, Fauzi Ali; Agustina, Agustina; Amin, Ghazali; Arlianti, Nopa (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2024)
Background: Based on Pidie Regent Regulation no. 5  year 2018, states that prospective brides and grooms (Catin) must have their health checked at all nearest health service centers to prevent transmission of infectious diseases (HIV, Hep B, Syphilis),and  treated  if they are at risk of disease, detect early reproductive Catin health problems  with laboratory examinations and premarital counseling. Compliance with prospective brides and grooms in carrying out health checks at the Pidie Regency level is 67%, while at the Mutiara Barat Community Health Center level at the average of 42.5% for HIV and Hep B checks, 40.4% for syphilis checks, and 10.7% for TT screening and 10% did the Plano test. The aim of this research is to see the level of Catin compliance in laboratory examinations and premarital counseling in the Mutiara Barat Health Center Working Area, Pidie Regency in 2019. Method: This research was conducted using a descriptive analytical, crosssectional design method. The population was all 214 prospective brides and grooms registered in the bride and groom report book at the Mutiara Barat Community Health Center. Sampling used a purposive sampling technique. Data analysis used the Chi Square test of the SPSS version 20. Result: The results of the study showed that there were no relationship between Catin's age and premarital examination (p value=0.384), Catin's education (p value=0.755), Catin's job (p value=1.000), availability of laboratory medical equipment (p value=0.330), and area of residence (p-value=0.153). Meanwhile, the gender variable has a significant relationship with laboratory examinations and premarital counseling (p value=0.018). Recommendation: It is hoped that the Puskesmas will collaborate across programs and across sectors to provide innovations that will make Catin more compliant with existing inspections.